2022
DOI: 10.1099/mgen.0.000758
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the genomic potential of Pseudomonas type strains for discovering new natural products

Abstract: Microbes host a huge variety of biosynthetic gene clusters that produce an immeasurable array of secondary metabolites with many different biological activities such as antimicrobial, anticarcinogenic and antiviral. Despite the complex task of isolating and characterizing novel natural products, microbial genomic strategies can be useful for carrying out these types of studies. However, although genomic-based research on secondary metabolism is on the increase, there is still a lack of reports focusing specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
1
6
1
Order By: Relevance
“…Additionally, a weak but significant positive correlation is observed between genome size and the number of BGCs per genome (r2 = 0.4538, p-value =<0.0001) (Fig. 1b), indicating an increase in the number of BGCs with a larger genome size, consistent with previous reports [41,42].…”
Section: Resultssupporting
confidence: 91%
“…Additionally, a weak but significant positive correlation is observed between genome size and the number of BGCs per genome (r2 = 0.4538, p-value =<0.0001) (Fig. 1b), indicating an increase in the number of BGCs with a larger genome size, consistent with previous reports [41,42].…”
Section: Resultssupporting
confidence: 91%
“…In this study, the genome mining of P. vancouverensis identified several biosynthetic gene clusters (BGCs), predominantly predicted to produce NRPs or NRP-like metabolites, as Saati-Santamaria et al [ 79 ] reported. All predicted BGCs shared less than a 50% identity with previously reported gene clusters except for one BGC (NRP-like) that was 100% identical to bovienimide-A, a synthetase produced by Xenorhabdus bovienii [ 38 ] ( Table 3 ).…”
Section: Discussionmentioning
confidence: 98%
“…Genomic mining strategies have been used for exploring natural products in Planomonospora ( 15 ), Pseudomonas ( 16 ), and Nocardia ( 17 ). In our previous study, metagenomic mining was performed ( 14 ), and a novel two-component bacteriocin, acidicin P, was identified from P. acidilactici .…”
Section: Discussionmentioning
confidence: 99%